EP826 Unchanged morbidity despite increased surgical radicality in cytoreductive surgery for an advanced stage epithelial ovarian cancer. (1st November 2019) - Kaufmann, A; Laios, A; Broadhead, T; Hutson, R; Nugent, D; Thangavelu, A; Theophilou, G; De Jong, D
Abstract : Introduction/Background: The surgical aim in cytoreduction for an advanced stage of ovarian cancer is to achieve complete cytoreduction (nil macroscopic disease) with minimal peri- and postoperative morbidity. We assessed the impact of the extent and complexity of surgical cytoreduction on morbidity in patients with an advanced stage of ovarian cancer. Methodology: A cohort of patients with a diagnosis of advanced stage (FIGO III/IV) high grade epithelial ovarian cancer, undergoing upfront and delayed surgical cytoreduction, from Jan 2016 to Dec 2018 was selected from the ovarian database. We evaluated age, surgical complexity score (SCS) and postoperative morbidity. The SCS was assigned based on the Aletti classification as low, moderate and high. Morbidity was graded based on the Clavien-Dindo score and grouped as 0, I–II, IIIA–IVB and V. The chi square test was used for statistical analysis. Results: 283 patients were identified. Mean age was 64±11 yrs. The median SCS was 3 (1–10). The number of patients identified with Clavien-Dindo 0 (no change from normal postoperative course), I–II (any simple deviation from the post-OP course or pharmacological treatment) and IIIa–IVB (intervention or life-threatening complications) were 134, 129 and 20 respectively. None of the patients died within 30-days post-operatively (Clavien-Dindo V).The SCS increased over the years 2016–2018 (p=0.0035) whilst the Cavien-Dindo remained unchanged (p=0.764; NS). Conclusion: We observed that in our cohort of patients with an advanced stage of ovarian cancer, increased surgical complexity does not result in increased surgical morbidity. Therefore radical surgery for an advanced stage of ovarian cancer, to achieve complete cytoreduction, seems justified in our population. Further monitoring and evaluation is ongoing Disclosure: Nothing to disclose.